Asymptotic symmetries and memories of gauge theories in FLRW spacetimes - Martín Enríquez Rojo; Tobias Schröder (Journal of High Energy Physics, 2023)
Abstract In this paper, we investigate the asymptotic structure of gauge theories in decelerating and spatially flat Friedmann-Lemaître-Robertson-Walker universes. Firstly, we thoroughly explore the asymptotic symmetries of electrodynamics in this background, which reveals a major inconsistency already present in the flat case. Taking advantage of this treatment, we derive the associated memory effects, discussing their regime of validity and differences with respect to their flat counterparts. Next, we extend our analysis to non-Abelian Yang-Mills, coupling it dynamically and simultaneously to a Dirac spinor and a complex scalar field. Within this novel setting, we examine the possibility of constructing Poisson superbrackets based on the covariant phase space formalism.